GÊNEROS DIGITAIS EMERGENTES EM LIVROS DIDÁTICOS DE LÍNGUA PORTUGUESA: um estudo de caso da cidade de Araçatuba/SP - TAÍS CRISTINA DE ARAÚJO DOS PASSOS (2023)
This master's thesis aims to identify and analyze approaches to digital genres in Portuguese language textbooks (2021/2022) that are part of the National Textbook Program (Programa Nacional do Livro Didático) and the Curriculum in Action Program (Programa Currículo em Ação), by the Department of Education of the State of São Paulo (SEDUC-SP), aimed at students in the 5th year of elementary school, generally aged between 10 and 11 years old, in the municipality of Araçatuba/SP. In addition, it is also offered a proposal for a didactic sequence of this type of genre. The study is justified by the need for and importance of understanding the tools linked to digital media and the teaching strategies of digital genres in Portuguese, enabling the dialogue between the teaching of the discipline and the empirical reality of the students. In this sense, there is a broader tangibility that articulates important aspects of the daily life of students and teachers in the classroom, listing pivotal aspects of language in digital spaces and digital genres in constant transformation and development. Thus, by achieving the established objective, this study identifies genres associated with different social media in the aforementioned Portuguese language teaching materials. From this selection, I present a critical comparative analysis of three teaching sequences used by such textbooks (one from each book) and methodologies applied in teaching such genres. In this sense, the theoretical and methodological assumptions to be used in linguistic analysis are Applied Linguistics, Multimodality, Internet Linguistics, Internet Applied Linguistics, Visual Design Grammar, and Content Analysis. The research it is of a critical and qualitative nature and will use excerpts extracted from selected teaching materials as data, highlighting the presence of digital genres in these materials. Thus, it was possible to articulate the theoretical-conceptual assumptions, focusing the discussion on the study of language and its particularities in the digital media environment and its application in the school space in Portuguese Language classes in Elementary School. The results indicated that the analyzed textbooks present significant differences between them, displaying a greater or lesser incidence of the digital genres in their contents. However, there is an overall understanding that books could present greater depth in the definition and compositional features of digital genres, as well as an approach in their teaching centered on their linguistic aspects and discursive purposes, consequently enabling meaningful interlocutions between the learning and daily experiences of students. Keywords: Digital Media; Textbooks Portuguese Language; Multimodality; Internet Linguistics; Linguistics Applied to the Internet.